GOOD CORPORATE GOVERNANCE TERHADAP SUSTAINABILITY REPORTING - Yenny Purbandari; Ratna Suryani (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
This study aims to examine the effect of the board of directors and audit committee on sustainability reporting. This research was conducted using a quantitative approach. The population of this research is companies that issue sustainability reporting which are listed on the Indonesia Stock Exchange during 2014-2017. The sample of this research is 80 taken by purposive sample method. Based on the results of multiple regression analysis for the board of directors and audit committee, it was obtained an adjusted R2 value of 20.5%. Based on the research results, it can be concluded that, first, the board of directors has no effect on sustainability reporting. The two audit committees have an effect on sustainability reporting.